Spectral Engineering of Semitransparent Polymer Solar Cells for Greenhouse Applications - Shi, Hui; Xia, Ruoxi; Zhang, Guichuan; Yip, Hin‐Lap; Cao, Yong (Advanced energy materials, 2019)
In this study, a wavelength selective semitransparent polymer solar cell (ST‐PSC) with a proper transmission spectrum for plant growth is proposed for greenhouse applications. A ternary strategy combining a wide bandgap polymer donor with a near‐infrared absorbing nonfullerene acceptor and a high electron mobility fullerene acceptor is introduced to achieve PSCs with power conversion efficiency (PCE) over 10%. The addition of PC71BM into J52:IEICO‐4F binary blend contributes to the suppressed trap‐assisted recombination, enhanced charge extraction, and improved open‐circuit voltage simultaneously. ST‐PSC based on the J52:IEICO‐4F:PC71BM ternary blend shows an optimized performance with PCE of 7.75% and a defined crop growth factor of 24.8%. Such high‐performance ST‐PSC is achieved by carefully engineering the absorption spectrum of the light harvesting materials. As a result, the transmission spectra of the semitransparent devices are well‐matched with the absorption spectra of the photoreceptors, such as chlorophylls, in green plants, which provides adequate lighting conditions for photosynthesis and plant growth, and therefore making it a competitive candidate for photovoltaic greenhouse applications. Spectral engineering and ternary blend approaches were employed to demonstrate an efficient semitransparent polymer solar cell tailored for greenhouse application. The semitransparent device transmits mainly blue and red lights for photosynthesis, and shows a high efficiency of 7.75% with a crop growth factor of 24.8%. Optimal sunlight harvesting in photovoltaics and photosynthesis will be beneficial for future greenhouse application.